2010
DOI: 10.1002/hrm.20335
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ethicality of firing employees who blog

Abstract: This exploratory study evaluates the ethical considerations related to employees fi red for their blogging activities. Specifi cally, subject evaluations of two employee-related blogging scenarios were investigated with established ethical reasoning and moral intensity scales, and a measure of corporate ethical values was included to assess perceptions of organizational ethics. The fi rst scenario involved an employee who was fi red because of innocuous blogging, while the second vignette involved an employee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Several other dimensions of moral intensity exist, including ''proximity'' that is based on the closeness one feels for individuals hurt by unethical conduct, ''probability of harm'' that involves the likelihood of adversely affecting others, and ''concentration of effect'' that isolates the potency of an unethical action (Jones, 1991). These factors work together to increase perceptions of moral intensity, which enhance the steps of the ethical decision-making process by strengthening sensitivity to the attributes of an ethical situation (e.g., Barnett, 2001;Barnett and Valentine, 2004;Carlson et al, 2002;Jones, 1991;Singhapakdi et al, 1996Singhapakdi et al, , 1999Valentine et al, 2010). Previous research indeed supports the proposed connection between moral intensity and ethical reasoning.…”
Section: Moral Intensity and Ethical Reasoningmentioning
confidence: 94%
See 1 more Smart Citation
“…Several other dimensions of moral intensity exist, including ''proximity'' that is based on the closeness one feels for individuals hurt by unethical conduct, ''probability of harm'' that involves the likelihood of adversely affecting others, and ''concentration of effect'' that isolates the potency of an unethical action (Jones, 1991). These factors work together to increase perceptions of moral intensity, which enhance the steps of the ethical decision-making process by strengthening sensitivity to the attributes of an ethical situation (e.g., Barnett, 2001;Barnett and Valentine, 2004;Carlson et al, 2002;Jones, 1991;Singhapakdi et al, 1996Singhapakdi et al, , 1999Valentine et al, 2010). Previous research indeed supports the proposed connection between moral intensity and ethical reasoning.…”
Section: Moral Intensity and Ethical Reasoningmentioning
confidence: 94%
“…Finally, behavior is often exhibited, which supports or reinforces the previously established steps (Jones, 1991;Rest, 1986). Previous studies show that these steps are positively related (Barnett and Valentine, 2004;Fleischman et al, 2007;Singhapakdi et al, 1996Singhapakdi et al, , 1999Singhapakdi et al, , 2000Valentine and Barnett, 2007;Valentine et al, 2010), and that the various stages are influenced by a variety of factors found within individuals, situations, and organizational contexts (Ford and Richardson, 1994;Loe et al, 2000;O'Fallon and Butterfield, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…However, there is no way for any respondent to ascertain whether an organization would actually experience such outcomes, and thus this measure's construct validity seems doubtful in that it does not assess "magnitude (or even probability) of organizational effect", and certainly not in the way intended by Jones (1991); that is, as objective attributes of situations. Similarly, there seems no way for any individual to provide meaningful estimates concerning the likelihood of formal sanctions or other outcomes (Smith et al, 2007, p. 646), the extent of perceived "moral intensity" (a composite of Jones' situational characteristics as determined by respondents; e.g., Chen, Pan, and Pan, 2009;Valentine and Fleischman, 2003;Valentine, Fleischman, Sprague, and Godkin, 2010;Valentine and Bateman, 2011;Vitell, Bakir, Paolillo, Hidalgo, Al-Khatib, and Rawwas, 2003), or any component characteristic such as "temporal immediacy" (whether anticipated consequences of the questionable action in the vignette would occur immediately or much later) or "proximity" (to what extent are those affected by questionable actions similar to respondents themselves).…”
Section: Respondent Determined Situational Characteristicsmentioning
confidence: 99%
“…A strong word of caution for anyone unhappy or disgruntled about others: save your vitriol and avoid taking grievances onto the blogosphere. Some employee bloggers, for example, have been fired for saying things about their bosses, and violating codes of confidentiality and non-disclosure agreements [13]. To keep your job, learn what can and cannot be said whenever you venture out onto the blogosphere.…”
Section: What Is a Blog?mentioning
confidence: 99%